Potential of 10 types of eucalyptus clones in the concession area PT TPL TBK Simalungun Indonesia - Sihombing, Benteng H (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
A researched 10 clones of Eucalypts were done in Toba Pulp Forest in 2 sectors of Aek Nauli and Tele as the representative plots. The main objective of the study was to determine the relationship between the number of trees and the average diameter, average branch-free height and average volume of 10 IND clones currently cultivated. in the plantation forest area of PT Toba Pulp Lestari Tbk and compared the volume of wood from 10 IND clones and determined the 3 candidate species recommended for cultivation in the next period. Research method of inventory of stand by circle radius plot of 11.28 m (0.04 ha) with 3 replications summarized plot broaded about 1.2 ha. Based on the wood analysis volume analysis can be resumed that 3 IND eucalypts clones are recommended for planting the next period, namely IND 61, IND 60 and IND 11.